2014
DOI: 10.1111/apa.12759
|View full text |Cite
|
Sign up to set email alerts
|

The effects of olfactory stimulation and gender differences on pain responses in full‐term infants

Abstract: Crying and finger splaying/fisting were observable responses that may be useful for screening pain or distress in healthy neonates. Increased pain reactions by boys may reflect higher irritability. Exposure to an unfamiliar odour did not have a calming effect on full-term neonates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…Sadathosseini observed that crying lasted significantly less and that variation in SatO 2 was lower when the odor of VEO was familiar [40]. Other studies have found no effects of VEO in soothing pain in full-term infants if the patients have not been previously exposed to this odor [26]. Neshat et al found no differences on prematures' heart rate and SatO 2 during venipuncture even though the neonates had been previously familiarized with VEO [25].…”
Section: Discussionmentioning
confidence: 98%
“…Sadathosseini observed that crying lasted significantly less and that variation in SatO 2 was lower when the odor of VEO was familiar [40]. Other studies have found no effects of VEO in soothing pain in full-term infants if the patients have not been previously exposed to this odor [26]. Neshat et al found no differences on prematures' heart rate and SatO 2 during venipuncture even though the neonates had been previously familiarized with VEO [25].…”
Section: Discussionmentioning
confidence: 98%
“…Regarding the upper limbs, Romantsik et al 25 showed that facial expressions, hand movements, and duration of crying in full-term newborns are useful for recognizing acute pain in healthy neonates. In preterm infants, flexion of the arms and legs, extension of the legs, opening the fingers and moving the hand toward the face were associated with the pain elicited by a heel prick.…”
Section: Discussionmentioning
confidence: 99%
“…Sadathosseini observed that crying lasted signi cantly less and that variation in SatO2 was lower when the odor of VEO was familiar [38]. Other studies have found no effects of VEO in soothing pain in full-term infants if the patients have not been previously exposed to this odor [24]. Neshat et al found no differences on prematures' heart rate and SatO2 during venipuncture even though the neonates had been previously familiarized with VEO [23].…”
Section: Discussionmentioning
confidence: 99%
“…Our hypothesis was that signs of pain (mostly crying time and NIPS score) would be lower in the experimental group than in the control group. We chose LEO and VEO because these are the fragrances for which more studies have been performed in neonates and infants [3,4,6,12,17,[19][20][21][22][23][24][25][26][27]. As far as we know, there are no previous studies which have analyzed the potential bene t of LEO vs VEO to relieve pain in neonatal frenotomy.…”
Section: Introductionmentioning
confidence: 99%